Drivers’ Behavior and Attitudes Towards Home Quarantine During the Corona Pandemic (Covid 19): Comparison between Gender and Education Level Variables - Alameri, Jamal; Alomosh, Ahmad (Al-Adab Journal, 2023)
The Corona pandemic has been an epidemiological and psychological crisis in which the difficulty of living in isolation, the changes that have taken place in our daily lives, the loss of a large number of individuals of their jobs, the financial hardship, and the grief over the death of loved ones, have affected the mental health and well-being of many. Despite the large number of studies that dealt with the impact of the Covid-19 pandemic on road accidents, they did not address the behavioral patterns of drivers during the home quarantine and what their attitudes are towards it. In addition to the significant differences in that according to gender and level of education. This study aimed to reveal the nature of drivers’ behaviors and attitudes towards home quarantine during Covid-19. And to identify the differences based on sex and education level between drivers in their behaviors and their attitudes towards home quarantine. The study tool included a questionnaire that includes phrases showing the behaviors of drivers in the United Arab Emirates during the home quarantine and their attitudes towards it. Six hundred and thirty-six 636 male and female drivers from the United Arab Emirates participated in answering the study tool. The results showed that the drivers responded to the home quarantine through positive behaviors and attitudes. The results showed that female drivers were more committed, but the differences were not statistically significant with their male drivers. However, the level of education has contributed to creating significant differences in a number of behaviors in favor of those with university education and above. The participants confirmed the safety of the measures taken by the United Arab Emirates to limit the spread of the Covid-19 pandemic.